2018
DOI: 10.3390/s19010002
|View full text |Cite
|
Sign up to set email alerts
|

ePhysio: A Wearables-Enabled Platform for the Remote Management of Musculoskeletal Diseases

Abstract: Technology advancements in wireless communication and embedded computing are fostering their evolution from standalone elements to smart objects seamlessly integrated in the broader context of the Internet of Things. In this context, wearable sensors represent the building block for new cyber-physical social systems, which aim at improving the well-being of people by monitoring and measuring their activities and provide an immediate feedback to the users. In this paper, we introduce ePhysio, a large-scale and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Finally, the continuous acquisition and storage of the patient physiological parameters (number of FOG episodes, FOG phenotype and muscle activity type) permits the development of an up-to-date electronic agenda, specific for each patient, thus opening to telemedicine applications, including tele-rehabilitation. Several studies [ 70 , 71 , 72 , 73 ] have already shown practical perspectives of wearable sensors use in the home environment to remotely monitor patients’ clinical state and improve therapeutic strategies. The objective and long-term measures by means of wearable sensors in free living-like conditions would support patients’ physical activity by giving feedback about motor performance and tailored instructions [ 74 ], such as lengthen the stride length during walking to limit the sequence effect (step-to-step decrease in amplitude) and thus potentially reduce FOG occurrence [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the continuous acquisition and storage of the patient physiological parameters (number of FOG episodes, FOG phenotype and muscle activity type) permits the development of an up-to-date electronic agenda, specific for each patient, thus opening to telemedicine applications, including tele-rehabilitation. Several studies [ 70 , 71 , 72 , 73 ] have already shown practical perspectives of wearable sensors use in the home environment to remotely monitor patients’ clinical state and improve therapeutic strategies. The objective and long-term measures by means of wearable sensors in free living-like conditions would support patients’ physical activity by giving feedback about motor performance and tailored instructions [ 74 ], such as lengthen the stride length during walking to limit the sequence effect (step-to-step decrease in amplitude) and thus potentially reduce FOG occurrence [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring correctness and irregularities in patterns different from normalprototype, identification of setbacks and unwarranted behavior [1,4] . Regular association between health information being transferred to health care professionals as exact and confirmative values [5] . Data stored in the sensors to be transferred and expanded to provide visual and auditory feedback to subjects [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The application of ML methods to study data from human movements and activities to detect and understand these activities are referred to as human activity recognition (HAR). In recent years, many ML and deep learning-based models have been used along with wearable sensors in the assessment of human movement activities in many domains including: health [ 11 ], recreation activities [ 12 ], musculoskeletal injuries or diseases [ 13 ], day-to-day routine activities (e.g., walking, jogging, running, sitting, drinking, watching TV) [ 11 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], sporting movements [ 22 ] and exercises [ 23 , 24 , 25 , 26 , 27 ]. The ML models used for exercise recognition have predominantly used multiple wearable sensors [ 28 , 29 , 30 , 31 ], specifically in the areas of free weight exercise monitoring [ 32 ], the performance of lunge evaluation [ 24 ], limb movement rehabilitation [ 33 ], intensity recognition in strength training [ 34 ], exercise feedback [ 24 ], qualitative evaluation of human movements [ 28 ], gym activity monitoring [ 29 ], rehabilitation [ 23 , 25 , 33 , 35 ] and indoor-based exercises for strength training [ 36 ].…”
Section: Introductionmentioning
confidence: 99%